Evaluating the semantic transparency of Guaraná: A domain‐specific language for enterprise application integration. (20th October 2021) - Bocanegra, Jose; Frantz, Rafael Z.; Roos‐Frantz, Fabricia; Basso, Fabio P.
Abstract: Guaraná domain‐specific language is aimed to design enterprise application integration models. Although the language has been broadly used in the industry and academy, the design of its graphical notation was based in the common sense and social opinion of its developers rather than theoretical principles and empirical evidence. Thus, Guaraná becomes as an option for studying, modifying, and improving its concrete syntax. In this article we conducted an experiment with 85 participants in order to evaluate the semantic transparency of the concrete syntax of Guaraná. The study concludes that the language is not found to be semantically immediate because most of the language constructs used in the graphical notation of Guaraná are not semantically immediate, that is, a novice reader is not able to infer their meaning from their appearance alone.